A binary mixed polymer brush coating with adjusted hydrophobic property to control protein adsorption. Issue 6 (8th March 2021) - Chen, Chaoshi; Atif, Muhammad; He, Kang; Zhang, Miao; Chen, Lijuan; Wang, Yanmei
Abstract : Binary mixed polymer brushes based on PGMA- b -PNIPAM- b -PSt and PMOXA- r -GMA were used as thermoresponsive coating to control protein adsorption. Abstract : In this work, binary mixed polymer brushes based on poly[(2-methyl-2-oxazoline)- random -glycidyl methacrylate] (PMOXA- r -GMA) and poly(glycidyl methacrylate)- block -poly( N -isopropyl acrylamide)- block -polystyrene (PGMA- b -PNIPAM- b -PSt) were used as thermoresponsive coating to control protein adsorption. Firstly, PMOXA- r -GMA was synthesized via cationic ring opening polymerization of 2-methyl-2-oxazoline followed by its copolymerization with glycidyl methacrylate (GMA); PGMA- b -PNIPAM- b -PSt was synthesized by reversible addition–fragmentation chain transfer polymerization of GMA, N -isopropyl acrylamide, and styrene sequentially. Then the mixed brushes were fabricated successfully by spin coating the mixture of PMOXA- r -GMA and PGMA- b -PNIPAM- b -PSt solutions onto silicon or glass substrates followed by an annealing protocol using GMA segments as an anchor. Afterwards, the investigation for adjusting the hydrophobic property of mixed brushes was performed. The results showed that when the environmental temperature is lower than the lower critical solution temperature (LCST) of PNIPAM, the tethered PNIPAM blocks are swollen and could bring the hydrophobic PSt block with optimum molar mass to the surface; when the environmental temperature is higher than the LCST of PNIPAM, the PNIPAM blocks collapse and could bring the hydrophobic block inside the hydrophilic PMOXA grafted polymer layer. Finally, the protein adsorption on mixed polymer brushes was investigated using a fluorescein isothiocyanate-labelled protein assay and ellipsometrys. The results showed that under the optimum molar mass of PSt block, mixed brushes could adsorb proteins in large quantities below the LCST of PNIPAM, and display resistance to protein adsorption above the LCST of PNIPAM.